2019
DOI: 10.3390/app9122525
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Development Trends and Key 5G Photonic Technologies Using Patent Analysis

Abstract: In recent years, 5G photonic technology has gradually gained increased attention from scholars. However, studies on 5G photonic technology have mostly focused on technological discussions or market development research, but have failed to identify the relevant key technologies from a comprehensive perspective. In particular, 5G photonic technology is an interdisciplinary technology that could create considerable potential business opportunities in the future, therefore, identifying related key technologies is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Not only is patent analysis is a prerequisite to patent-based competitiveness, but it also provides companies with useful information for companies to develop their technological strategies, evaluate competitors, and anticipate market trends. Patent analysis is a uniquely practical analysis method for developing enterprise strategy and competition analysis, generating visual statistical reports to illustrate technical activities, and using life cycle models to predict patent development trends [53][54][55]. In this study, we analyze the development of 5G and blockchain through patent analysis technology.…”
Section: Patent Analysismentioning
confidence: 99%
“…Not only is patent analysis is a prerequisite to patent-based competitiveness, but it also provides companies with useful information for companies to develop their technological strategies, evaluate competitors, and anticipate market trends. Patent analysis is a uniquely practical analysis method for developing enterprise strategy and competition analysis, generating visual statistical reports to illustrate technical activities, and using life cycle models to predict patent development trends [53][54][55]. In this study, we analyze the development of 5G and blockchain through patent analysis technology.…”
Section: Patent Analysismentioning
confidence: 99%
“…Other specific sectors of activity where 5G is considered to be a key enabling technology are healthcare, the automation of vehicles, industrial manufacturing, logistics and smart farms (Anwar and Prasad 2018). In addition, the increased speed and the lower latency will support more efficient data transmission through improved network coverage and capacity, and thus will foster the efficiency of tools, such as augmented reality, and many other activities and personal experiences that need strong data transmission that were limited by insufficient speed, stability and latency with 4G (Hsieh, 2018;Chang, 2019).…”
Section: The Evolution Of "Generations" Of Technologies In Mobile Commentioning
confidence: 99%
“…Patents, notwithstanding the acknowledged limitations that they do not account for all the innovations produced, are largely recognised as being a good proxy for innovation at the aggregate level (Acs et al, 2002;Burhan et al, 2017). Several studies are inquiring into the relevance of technological specialisations for the market development of specific 5G technologies, such as the "5G photonic" (Chang, 2019), or the "network function virtualization" (Hu and Guo, 2019), however, to the best of our knowledge, there are a lack of studies that are related to the technological development of 5G using a 3 Diversity indicates how many different technological specialisations are present in an area, region or country, while ubiquity defines how rare these technological specialisations are. broader perspective (Noh et al, 2016).…”
Section: The Databasementioning
confidence: 99%
See 1 more Smart Citation
“…As a key outlet for scientific and technological development, 80% of technical items can be found in patent information [10]. The main applications of patent information include identifying the main competitors, tracking the development trend of technology, assessing the capabilities of the technological innovation or helping organizations to formulate patent strategy and planning [11][12][13]. Karvonen et al indicated that patent information is a valuable source for displaying the development trend of a given technology and assessing the status quo of potential competitors, and the analysis of patent information is crucial to identify TC in a given technology field [14].…”
Section: Introductionmentioning
confidence: 99%